Electronic Medical Record and Smoking Cessation Activities: Literature Review - Sutha, Diah Wijayanti; Nudji, Bambang; Faida, Eka Wilda; Christine, Christine (International Journal of Health and Information System, 2024)
Vital information regarding the life and health of a patient is gathered in medical records. The electronic medical record (EMR) is the product of medical record information technology development. Electronic health records and other health information systems have the potential to be useful tools for raising the caliber and efficacy of clinical interventions aimed at reducing tobacco consumption. Electronic medical records are used by doctors, clinics, and health care organizations to track patient smoking cessation outcomes and as a smoking cessation support tool. Thirteen papers from the Google Schoolar database and the reference lists of the included research were used in the review. We looked for research that was written between 2010 and 2020. Overall, these trials discovered that only slight benefits were made by several doctor-recommended therapies related to tobacco use. Following modifications to electronic medical records intended to speed up the collection and management of tobacco use during medical visits, there seems to have been a rise in the documentation of tobacco status and referrals for cessation counseling. To maximize the potential of EMRs for extra therapeutic advantages and smoking cessation in hospital settings, more research is required.